Inhibitory effects of functionalized polycarboxylate retarder on aberrant thickening phenomena of oil well cement at high temperature. (8th March 2021) - Zhang, Hang; Hu, Miaomiao; Xu, Yang; Xia, Xiujian; Zhang, Chi; Yu, Yongjin; Feng, Yakai; Guo, Jintang
Graphical abstract: Highlights: Functionalized polycarboxylate retarder (PAINM) was synthesized and characterized. Aberrant thickening phenomena of oil well cement at high temperature were inhibited. Inhibitory effects of PAINM on aberrant thickening phenomena were analyzed. Properties of cement slurry with retarder PAINM were investigated. Abstract: Aberrant thickening of cement slurry caused by polycarboxylate retarders mainly refers to abnormal gelation and thickening time reversal (TTR) when temperature reaches above 120 °C. These phenomena would directly jeopardize cementing operation and hinder the application of polycarboxylate retarders in oil and gas exploitation. Herein, two functionalized polycarboxylate retarders were synthesized to overcome the challenges in complex conditions. The incorporation of isoprenyl oxy poly(ethyleneglycol) ether (TPEG) and [3-(methacryloylamino) propyl] trimethyl ammonium chloride (MAPTAC) was capable of preventing unfavorable "crosslinking and chelation" reaction between cement grains and polymer, thereby avoiding abnormal gelation. It was also found that the hydrophobic association behavior of long side chain in TPEG could cause the gradual release of carboxyl groups at elevated temperature, which was unfavorable for TTR inhibition. When the TPEG was replaced by N-Vinyl-2-Pyrrolidinone (NVP), its retarding effect gradually weakened when temperature rose from 130 °C to 150 °C, and excellent inhibition of TTR was achieved.